Aging and the Perception of Motion-Defined Form. (January 2020) - Norman, J. Farley; Sanders, Karli N.; Shapiro, Hannah K.; Peterson, Ashley E.
A single experiment required 26 younger and older adults to discriminate global shape as defined only by differences in the speed of stimulus element rotation. Detection of the target shape required successful perceptual grouping by common fate. A considerable adverse effect of age was found: In order to perceive the target and discriminate its shape with a d ' value of 1.5, the older observers needed target element rotational speeds that were 23.4% faster than those required for younger adults. In addition, as the difference between the rotation speeds of the background and target stimulus elements increased, the performance of the older observers improved at a rate that was only about half of that exhibited by the younger observers. The results indicate that while older adults can perceive global shape defined by similarity (and differences) in rotational speed, their abilities are nevertheless significantly compromised.